Un libro de secretos : hijas ilegítimas, padres ausentes - Holroyd, Michael; Barba, Andrés, 1975-; Holroyd, Michael (Madrid : Siruela, 2015)
The author shares the stories of unknown women who played significant roles in the lives of prominent figures, including a mistress shared by the second Lord Grimthorpe and the Prince of Wales (Alice Keppel), a creative muse of Auguste Rodin (Eve Fairfax), and a novelist lover of Vita Sackville-West (Violet Trefusis). He also reflects on himself as investigator and biographer.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed April 14, 2017)
Keywords: Trefusis, Violet, -- 1894-1972.; Fairfax, Evelyn Constance, -- 1871-1978.; Keppel, Alice, -- 1869-1947.; Women -- Biography; Gifted women -- Biography; Daughters -- Biography; Illegitimate children -- Biography; Absentee fathers -- Biography; Unmarried mothers -- Biography; Mistresses -- Biography; Fathers and daughters; Electronic books